2021
DOI: 10.1007/s10787-021-00810-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk of mortality in patients with COVID-19 with pre-diagnosis use of NSAIDs: a meta-analysis

Abstract: The notion that the use of non-steroidal anti-inflammatory drugs (NSAIDs) may lead to adverse outcomes upon acquisition of coronavirus disease 2019 (COVID-19) should be discredited with a review of the real-life evidence. We aimed to perform a meta-analysis to summarize the risk of mortality with the preadmission/pre-diagnosis use of NSAIDs in patients with COVID-19. A systematic literature search was performed to identify eligible studies in electronic databases. The outcome of interest was the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Large meta-analyses have shown that neither RAAS, nor other antihypertensive drugs, nor NSAIDs are associated with increased risk of death. The reason for previous observations was not the influence of drugs on COVID-19, but it was the effect of underlying comorbidities alone [19,20]. Moreover, statins, due to their anti-inflammatory effect, are associated with lower risk of fatal COVID-19 [21][22][23] among non-ICU patients and lower risk of mechanical ventilation treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Large meta-analyses have shown that neither RAAS, nor other antihypertensive drugs, nor NSAIDs are associated with increased risk of death. The reason for previous observations was not the influence of drugs on COVID-19, but it was the effect of underlying comorbidities alone [19,20]. Moreover, statins, due to their anti-inflammatory effect, are associated with lower risk of fatal COVID-19 [21][22][23] among non-ICU patients and lower risk of mechanical ventilation treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of the studies were conducted in patients with COVID-19 or SARS-CoV-2 infection, and the number of participants ranged from 103 to 2.74 million. In addition, a meta-analysis that included 2414 patients from three studies was retrieved 29 .…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Kow and Hasan included data from 2414 patients across three studies that compared COVID-19 patients who were users or non-users of NSAIDs 29 . A pooled HR of 0.86 (95% CI 0.49–1.51) demonstrated no significant difference in the risk of fatality between NSAID users and non-NSAID users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 Several meta-analyses have shown that using NSAIDs, including ibuprofen, does not increase the risk of serious complications such as severe acute respiratory distress syndrome (ARDS), hospitalization, ICU admission, and death, in patients both confirmed and suspected of SARS CoV-2 infection. 75 , 76 …”
Section: Drug Used For Self-medication In Covid-19mentioning
confidence: 99%